Nova IMS Contribution for SDGs achievement: A Business Intelligence Approach - Chande, Iara Belinda Bugalho (2022)
Project Work presented as the partial requirement for obtaining a Master's degree in Information Management, specialization in Knowledge Management and Business Intelligence